Policy Asymmetry and Persistence: Street Vendor Governance in Tangerang Regency - Dini Nuraini Mahalli; Ahmad Ahmad; Tri Cahya Indra Permana; Aris Gumilar (Indonesian Journal of Law and Policy Studies, 2023)
This inquiry examines the application of Regional Regulation No. 08 of 2015 on Structuring and Empowerment of Pedagang Kaki Lima (PKL) or Street Vendors in Tangerang Regency, with the critical case of Pasar Ceplak, Sukamulya District. Drawing on a qualitative descriptive approach, specifically a case study, this research highlights structural and operational constraints obstructing the implementation of the policy’s dual objectives by using the theory of policy implementation, as articulated by Van Metter and Van Horn. These findings demonstrate that their implementation has been consistently suboptimal, namely PKL persistence in unauthorized locations, and pervasive failures in planned relocation efforts. Such shortfalls are largely due to a dire lack of strategic resources, and the insufficient provision of alternative trading zones in the relevant departments which can reduce the economic risk to PKL. Moreover, through analyzing data, ineffective communication results in information asymmetry and the adoption of a punitive enforcement approach which is both systemic and entrenched rather than an empowerment strategy. Consequently, this study reveals that the policy is riddled with severe operational asymmetry, whereby vendors’ socio economic rationalities routinely contradict the regulatory mandate, calling for an immediate shift to participatory and spatially integrated systems of governance to enable sustainable urban order as well as micro-enterprises to grow.